2004
DOI: 10.1097/01.aog.0000109220.24211.bd
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive 1-Hour Glucose Challenge Test and Adverse Perinatal Outcomes

Abstract: A false-positive GCT is an independent risk factor for adverse perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 21 publications
3
62
0
1
Order By: Relevance
“…We confirmed that untreated maternal mild hyperglycemia (impaired GCT with one abnormal or no abnormal glucose value at OGTT) in otherwise young and healthy women in the US was associated with a 2-3 fold increased risk of delivering an LGA infant (table 2). These observations are consistent with previous findings from populations studied worldwide by the HAPO group and other studies (HAPO, 2008;Stamilio et al 2004). In addition, increased risk of LGA birth in GDM women (all of whom were treated by diet or with insulin) was associated with high maternal pre-pregnant BMI.…”
Section: What Do We Learn From the Camden Study?supporting
confidence: 92%
See 1 more Smart Citation
“…We confirmed that untreated maternal mild hyperglycemia (impaired GCT with one abnormal or no abnormal glucose value at OGTT) in otherwise young and healthy women in the US was associated with a 2-3 fold increased risk of delivering an LGA infant (table 2). These observations are consistent with previous findings from populations studied worldwide by the HAPO group and other studies (HAPO, 2008;Stamilio et al 2004). In addition, increased risk of LGA birth in GDM women (all of whom were treated by diet or with insulin) was associated with high maternal pre-pregnant BMI.…”
Section: What Do We Learn From the Camden Study?supporting
confidence: 92%
“…The prevalence of mild hyperglycemia (defined as abnormal plasma glucose concentration during glucose challenge test with a diagnostic oral glucose tolerance test (OGTT) that did not meet the criteria of GDM) in women screened for GDM was 32% in Caucasian women (Mello et al, 1997), 25% in MexicanAmericans (Yogev et al, 2004) and 9% in multiethnic US population where 70% were African American (Stamilio et al, 2004). The relatively high prevalence of less severe maternal hyperglycemia raises important questions about effects on the fetus since these women are not provided the usual diabetic care for GDM.…”
Section: Significance Of Mild Gestational Hyperglycemia and Lga Birthmentioning
confidence: 99%
“…The hospital-based studies conducted in the United States diagnosed GDM based on a 3-hour OGTT and report prevalence rates ranging from 2.7% using the NDDG criteria to 6.8% in a largely Mexican American population using the C & C criteria (89)(90)(91). In a Canadian study at the Saskatoon Royal University Hospital, using the NDDG criteria, the prevalence was 11.5% in the Aboriginal population and 3.5% in the non-Aboriginal population (92).…”
Section: Hospital-based Studiesmentioning
confidence: 99%
“…Two recent studies found that women with an abnormal GLT but negative GTT still had higher risk of preeclampsia, cesarean delivery, macrosomia, shoulder dystocia, and neonatal morbidities that are often associated with poor glycemic control. 45,46 As Carpenter and Coustan so eloquently stated, the relationship between carbohydrate intolerance and adverse perinatal outcome is a continuous one, and no single cutoff can truly separate those at high risk and those at no risk at all. 47 Thus, the cost of screening and diagnosis of GDM must be weighed against the benefits of treatment to achieve optimal perinatal outcomes for women with or at risk for GDM.…”
Section: Diagnosis Of Gdmmentioning
confidence: 99%